SOLAR CELLS WITH COMPUTER ANALYSIS: A PHYSICS-BASED REVIEW - Dr. Aloke Verma, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
This review highlights the role of physics in understanding solar cell operation and theuse of computer-based analytical tools for modeling, simulation, and optimization. Starting fromfundamental photovoltaic (PV) physics